Optimism of Women with Belis - Syawalia Nenak; Rizky Pradita Manafe; Marleny Purnamasari Panis (Journal of Health and Behavioral Science, 2026)
Marriage practices rooted in local cultural traditions often shape women’s psychological experiences and well-being. In the Nagekeo community, the ‘belis’ tradition not only represents social respect and cultural identity but also presents social, economic, and emotional challenges for women within marital life. This study aims to identify the factors that influence women's optimism with belis in Nagekeo, using a descriptive qualitative method with 7 participants. Data were collected through interviews and thematic analysis. The results found four main themes that shape women's optimism: (1) social support, including support from husbands, children, immediate family, and the social environment; (2) self-esteem that arises from social appreciation and acceptance after the belis process; (3) self-confidence through involvement in decision-making, adaptability, and self-control; (4) accumulated experience, including readiness for marriage and spiritual conviction. These findings show that women's optimism is shaped by mutually reinforcing factors that help them persevere and view marriage positively.